ACCOUNTING OUTSOURCING: CONTENT AND NEW REALITIES (INNOVATIVE ECONOMY, 2024)
Shmyhel O.Ye. ACCOUNTING OUTSOURCING: CONTENT AND NEW REALITIESPurpose. The aim of the article is to review the scientific interpretation of the concept of “accounting outsourcing” and its application in business processes of companies.Methodology of research. The research was conducted using a dialectical approach to the study of the current state of accounting development. General scientific and special methods are used, in particular: analysis, synthesis, induction, deduction and generalization as methods of scientific knowledge applied to the development of the provisions of the theory and practice of accounting outsourcing in the system of documentary and informational support of the main business processes of companies, monographic – when studying literary sources on accounting issues; epistemological method – to clarify and deepen the content of the “accounting outsourcing” category; system and analytical – when processing the received information; abstract and logical method – for formulating research conclusions.Findings. It was determined that in the conditions of decentralization of the company's business processes, introduction and development of new business concepts, approaches to the accounting methodology are changing, and the need to use accounting outsourcing is increasing. It is substantiated that the delegation of accounting responsibilities to specialized companies helps to change the functioning of the company's management and in accounting, in particular. It was found that the result of the development of accounting outsourcing will be the optimization of the organizational structure and functional capabilities of accounting, including through staff reduction, modernization of accounting processes and accounting policies in general; strengthening requirements for professional skills of users. Originality. A review of literary sources was carried out to clarify the meaning of the concept of “accounting outsourcing”, which made it possible to offer the latest understanding of the external accounting support of the company's business processes for the optimization of decentralized management functions.Practical value. The obtained results of the research will contribute to increasing the effectiveness of the formation and development of accounting outsourcing in modern conditions and will become the basis for further scientific developments in this field.Key words: accounting, accounting outsourcing, decentralization, business processes, specialized companies.
Keywords: accounting; accounting outsourcing; decentralization; business processes; specialized companies.